(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Energy drinks are among the most popular products among young people and people experiencing intense psycho-emotional and physical stress. Their increasing consumption has attracted the attention of specialists in the fields of medicine, hygiene, and public health. This article analyzes a student survey. The majority of respondents consume energy drinks, and the reasons for this are presented.